2008
DOI: 10.1189/jlb.0108043
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation by FasL and Apo2L/TRAIL in human T-cell blasts. Implications for autoimmune lymphoproliferative syndromes

Abstract: The Fas-FasL pathway plays an important role in the homeostasis of mature lymphocytes, with defects causing autoimmune lymphoproliferative syndromes (ALPS). Human T-cell blasts are not sensitive to FasL or Apo2L/TRAILinduced apoptosis unless they get reactivated, but either of those ligands inhibits their growth in the absence of cell death induction due to a cell cycle arrest in S-G 2 /M. In the present work, we have studied the mechanism(s) by which FasL or Apo2L/ TRAIL regulate T-cell blast cell cycle in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The same group confirmed this concept using Jurkat T cells (45). In a later study (4), Fas binding of human T cell blasts reduced their proliferation with a concomitant increase in p21, a finding that directly associates p21 with the antiproliferative mechanism of the Fas/FasL system. These studies reinforce the view that the Fas/FasL system attenuates proliferation, although Fas cross-linking in vitro could entail questions regarding the physiological relevance of these data.…”
Section: Etiology Of In Vivo Lpr T Cell Proliferationmentioning
confidence: 86%
See 4 more Smart Citations
“…The same group confirmed this concept using Jurkat T cells (45). In a later study (4), Fas binding of human T cell blasts reduced their proliferation with a concomitant increase in p21, a finding that directly associates p21 with the antiproliferative mechanism of the Fas/FasL system. These studies reinforce the view that the Fas/FasL system attenuates proliferation, although Fas cross-linking in vitro could entail questions regarding the physiological relevance of these data.…”
Section: Etiology Of In Vivo Lpr T Cell Proliferationmentioning
confidence: 86%
“…In a previous study, T cell blasts from ALPS patients with higher responses than controls showed lower p21 expression (4). We therefore overexpressed the cell cycle inhibitor p21 in B6/ lpr and MRL/ lpr mice in a T cell-specific manner.…”
Section: Reduction Of T Cell Hyperproliferation Regulates Lymphadenopmentioning
confidence: 86%
See 3 more Smart Citations